1993
DOI: 10.1002/jlb.54.3.259
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hypogravity and hypergravity on cells of the immune system

Abstract: This article reviews the gravity effects discovered in T lymphocytes and other cells of the immune system. The strong depression of mitogenic activation first observed in an experiment conducted in Spacelab 1 in 1983 triggered several other investigations in space and on the ground in the clinostat and in the centrifuge in the past 10 years. During this period, great progress was made in our knowledge of the complex mechanism of T cell activation as well as the technology to analyze the lymphokines produced du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 0 publications
5
75
1
Order By: Relevance
“…Especially for T lymphocytes, it is known that exposure of cells in culture to actual or modelled low gravity is often accompanied by a major inhibitory effect, remarkably reducing their mitogenic activation process (Cogoli et al 1984) and severely altering growth rate, cytokine production, gene expression, cytoskeletal structures, and motility (for reviews, see Cogoli 1993Cogoli and Cogoli-Greuter 1997;Lewis 2002;Cogoli-Greuter 2004). Furthermore, it has been demonstrated that human lymphocytes are forced to apoptosis in modelled low gravity, through a pathway based on calciumdependent 5-LOX activation, mitochondrial membrane disruption, and cytochrome c release, followed by caspase activation and cell death (Maccarrone et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Especially for T lymphocytes, it is known that exposure of cells in culture to actual or modelled low gravity is often accompanied by a major inhibitory effect, remarkably reducing their mitogenic activation process (Cogoli et al 1984) and severely altering growth rate, cytokine production, gene expression, cytoskeletal structures, and motility (for reviews, see Cogoli 1993Cogoli and Cogoli-Greuter 1997;Lewis 2002;Cogoli-Greuter 2004). Furthermore, it has been demonstrated that human lymphocytes are forced to apoptosis in modelled low gravity, through a pathway based on calciumdependent 5-LOX activation, mitochondrial membrane disruption, and cytochrome c release, followed by caspase activation and cell death (Maccarrone et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Clinostatic rotation is another system that is used to model microgravity for both plant and animal cells [5]. Specifically, clinostats were used to show a suppressed response of lymphocytes to concanavalin A (Con A) that correlated with a suppressed response observed during later orbital flight studies [6][7][8][9]. Clinostats compensate gravity by circular rotation about a horizontal axis, which causes the time-averaged gravitational force to be zero [10].…”
Section: Introductionmentioning
confidence: 99%
“…Astronauts in-flight of both long-and short-duration missions have a reduced delayed-type hypersensitivity skin test response [15][16][17]. Furthermore, in vitro experiments performed in both true and simulated microgravity demonstrate a suppressed response of lymphocytes to mitogens [6][7][8][9][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Early human studies indicated that space flight changed human cell culture activities, such as leukocyte blastogenesis ( [Cogoli et al, 1980], [Cogoli et al, 1984], [Bechler et al, 1992] and [Cogoli, 1993]), production of cytokines ([Talas et al, 1983] and [Bechler et al, 1992]) and signal transduction in leukocytes ([Limouse et al, 1991] and [Schmitt et al, 1996]). Studies on animal cell cultures have shown alterations in cytokine production (Chapes et al, 1992), and macrophage hematopoiesis and function (Armstrong et al, 1995).…”
Section: Combined Microgravity and Radiation Effectsmentioning
confidence: 99%